2016
DOI: 10.2147/ppa.s110419
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with lipid goal attainment among acute coronary syndrome patients

Abstract: BackgroundThe incidence of acute coronary syndrome (ACS), one of the most common cardiovascular diseases, is high. Lipid goal attainment is one of the important factors to reduce the risk of recurrent heart attack. Identification of factors influencing lipid goal attainment such as age, female, race, underlying comorbidities, intensity of lipid-lowering therapy, patients’ knowledge, and patients’ belief about medicine would be beneficial in achieving the lipid goal. This study is aimed to determine lipid profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…With the increase in age, ACS patients were less likely to reach LDL-C level < 70 mg/dl in our study, in contrast to previous reports. [ 32 33 34 ] Although the reason for this is not apparent, we did not reach any conclusion and suggested that additional studies are necessary to clarify these points specific to the Emirati population.…”
Section: Discussionmentioning
confidence: 68%
“…With the increase in age, ACS patients were less likely to reach LDL-C level < 70 mg/dl in our study, in contrast to previous reports. [ 32 33 34 ] Although the reason for this is not apparent, we did not reach any conclusion and suggested that additional studies are necessary to clarify these points specific to the Emirati population.…”
Section: Discussionmentioning
confidence: 68%